Korelasi Kepadatan Populasi Tiga Spesies Ikan Belanak dengan Beberapa Faktor Fisika Kimia Perairan - Khairul Khairul; Sri Mahdalena (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the density correlation of three species of mullet with the water’s physical and chemical parameters in the Barumun River. This explorative type of research using the purposive sampling method. Fish are caught using a gill net with a mesh size of 1 inch. Analysis of the research data was carried out using the SPSS version 22 application program. The results showed that there were three types of mullet fish caught in the Barumun River, namely Chelon subveridis, Moolgarda perusii and Liza alata. The bivariate correlation test analysis results showed that water transparency and pH showed a positive correlation (+), while temperature, current and salinity had a negative correlation (-). The highest positive correlation value is found in water transparency. In conclusion, the higher the water transparency value, the higher the density of the mullet fish. Keywords: Density, Belanak Fish, Water Quality, Correlation Test